The modified 5-item frailty index is a predictor of perioperative risk in breast reconstruction: An analysis of 40, 415 cases. Issue 9 (September 2022) - Panayi, Adriana C.; Foroutanjazi, Sina; Parikh, Neil; Haug, Valentin; Kauke-Navarro, Martin; Diehm, Yannick F.; Pomahac, Bohdan
Summary: Background: The aging population has presented surgeons with new challenges as they increasingly must operate on greater numbers of frail patients. The modified frailty index 5 (mFI-5) is a concise comorbidity-based scale that has been shown to accurately predict adverse surgical outcomes. In this study, we sought to evaluate the ability of the mFI-5 to predict the risk of postoperative outcomes in breast reconstruction patients. Methods: Utilizing the 2015–2019 American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database, we identified 40, 415 patients who underwent breast reconstruction, of which 29, 562 were implant-based reconstructions and 10, 853 were autologous breast reconstructions. Demographic and preoperative variables as well as 30-day postoperative outcomes, including mortality, operation duration, length of hospital stay, medical and surgical complications, and discharge destination, were extracted. Results: Increases in the mFI score correlated with higher rates of reoperation (mFI≥3: 13.5% vs. mFI=0: 5.9%), unplanned readmission (mFI≥3: 10.8% vs. mFI=0: 3.6%), surgical (mFI≥3: 12.2% vs. mFI=0: 4.3%) and medical complications (mFI≥3: 6.8% vs. mFI=0: 1.2%), and lower rates of home discharge (mFI≥3: 96% vs. mFI=0: 99.5%). Multivariate analysis to control for confounders verified significantly higher rates of reoperation (OR=0.01, 95%CI 0.005—0.016), unplanned readmission (OR=0.009, 95%CI 0.005—0.014), and occurrence of surgical complications (OR=0.014, 95%CI 0.009—0.019) and medical complications (OR=0.005, 95%CI 0.002—0.008). Stratification by age showed that the mFI-5 was a stronger risk predictor in younger patients who are frail. Stratification by type of reconstruction showed that increased mFI scores significantly correlated with complications in both autologous and implant-based reconstruction, but the correlation was greater in autologous procedures. Conclusion: The mFI-5 is identified as a powerful risk predictor in breast reconstruction. The application of this easily accessible tool in the preoperative risk stratification of patients undergoing breast reconstruction can enhance treatment planning and support, optimizing patient counseling, informed consent, and decision-making.